SOSIALISASI PEMBUATAN SUSU KELOR PROBIOTIK SEBAGAI PANGAN FUNGSIONAL - Aini Aini; Alfi Maulana; Siti Zaitun (Jurnal Pengabdian Masyarakat Sehati, 2023)
Gempur Senior School is a group of seniors who follow learning activities. The elderly group is also active in other activities such as gardening. The activities carried out by the elderly school is in the gardening producing cane crops that have been sold all this time in the form of vegetables. This dedication is aimed at socializing the method of making probiotic milk or "Morikult" to the elderly group for the manufacture of milk products by using a starter isolated by the chief servant and combining the stater with the powder produced by the senior group. This activity was followed by 40 members of the elderly group. This dedication was carried out for 8 days consisting of 4 days of material purchase including evaluation in the form of pretest and post test. The next 4 days are practical manufacturing activities. The indicator of success is by performing a capability evaluation based on an increase in pre-test and post-test values of 3.5. Given in the form of an interview system. The evaluation of psychomotor or practical activities is carried out by looking at the ability of the product resulting from the sense of consistency and other qualities determined by the serving team.